Profil Hematologi pada Ternak Sapi Bali (Bos Sondaicus) yang Dipelihara di Desa Tunbaun Kecamatan Amarasi Barat Kabupaten Kupang - Egenius Fernandez Aliandu; Yeremia Y Sitompul; Tarsisius C Tophianong; Yustinus O.P Wuhan (Jurnal Veteriner Nusantara, 2023)
The normal value of hematology in Balinese cattles (Bos Sondaicus) maintained in East Nusa Tenggara (NTT) is still very limited. The hematology data is usually used for various purposes, including knowing the status of animals' health, helping to uphold the diagnosis, and monitoring responses to therapies or developments in the pathogenesis state of the disease. The sample used in this study was blood collected from Bali cattle which were symptomatically healthy, male and female who were not pregnant, and the average age was 2 - 6 years. Bali cattle will be divided into 2 groups with a total of 15 male and 15 female cows. A blood hematology test using an auto hematology analyzer, Rayto type RT-7600. Statistical calculations are calculated using the SPSS 25.0 application. Based on data analysis, RBC, HB, HCT, MCV, MCH, MCHC, WBC, LYM, and GRA have a significant discrepancy based on gender because of a value of P> 0.05. Meanwhile, MID did not have a significant difference based on sex.